STRUCTURAL DISCREPANCIES IN PEDAGOGICAL QUALIFICATIONS BETWEEN STATE AND NON-STATE EARLY CHILDHOOD EDUCATION IN UZBEKISTAN (Multidisciplinary Journal of Science and Technology, 2026)
The cognitive efficacy of early childhood education relies intrinsically on the advanced academic qualifications of pedagogical personnel. Recent systemic expansions within Uzbekistan's preschool sector have exposed significant credentialing disparities between public and private institutions. This diagnostic study quantitatively and qualitatively investigates these stratifications utilizing a stratified random sampling of 1,422 active educators. Empirical findings indicate a dominant systemic reliance on secondary vocational credentials: 61.4% within state organizations versus an elevated 76.2% within non-state entities. Multivariate logistic regression evaluates the socioeconomic antecedents driving this phenomenon, revealing that private enterprises optimize for operational cost-efficiency over formal academic mandates, while public entities struggle with institutional retention and pipeline bottlenecks. The absence of synchronized continuous professional development pathways heavily restricts upward academic mobility. We propose robust institutional intervention frameworks, including state-subsidized micro-credentialing, localized academic bridging programs, and inter-sectoral qualification mandates, to ensure equitable cognitive developmental environments across all fiscal modalities.